Extra-pair fertilizations contribute to selection on secondary male ornamentation in a socially monogamous passerine - Albrecht, T; Vinkler, M; Schnitzer, J; Poláková, R; Munclinger, P; Bryja, J (Journal of evolutionary biology, 2009)
Despite considerable research effort, it remains unclear whether extra-pair fertilizations (EPF) drive the evolution of male secondary ornamentation in socially monogamous systems. In this study, we test the hypothesis that EPF contribute to the evolution or maintenance of male feather ornamentation in a sexually dichromatic passerine, the Scarlet Rosefinch, Carpodacus erythrinus. We show that the colouration of ornamental breast feathers is a good predictor of basic sources of variation in male annual reproductive output in rosefinches and that the annual realized reproductive success of males is positively associated with measures of ornamental colouration only when gains and losses because of EPF are considered. The results indicate that EPF in rosefinches may rely on absolute (good genes) rather than self referential (genetic complementarity) criteria of mate choice. Our study corroborates the potentially important role of EPF in the evolution and/or maintenance of elaborate male ornaments in socially monogamous taxa.
Keywords: Passeriformes; peří; Fertilization; fertilizace; mužské pohlaví; zvířata; Feathers; Sexual Behavior, Animal; sexuální chování zvířat; Male; Animals